Applying Whisper Game in Affecting Vocabulary Mastery at Eighth Grade of Junior High School - Efa Silfia; Ridho Praja Dinata (Universitas Batanghari Jambi, 2023)
This aim of this research was to see the effect of using whisper game towards students’ vocabulary mastery at eighth grade of SMPN 3 Kota Jambi, whether it has significant effect or not. The design of this research was an experimental research that was done in pre-test and post-test. Before getting the sample, the population, VIIIA, VIIIB and VIIIC class, were previously given homogeneity test. After the class population achieving homogenous, the class samples were taken by using cluster random sampling technique. Then, the data of this research was collected by using vocabulary test. Type of the test was matching choice. The implementation of whisper game in teaching vocabulary at eighth grade of SMPN 3 Kota Jambi was conducted to two classes; they were experimental class and control class. The participant of this research was 37 students, there were 19 students in experimental class, and 18 students were in control class. In collecting the data, they were given the same test. The data from the test was analyzed quantitatively by using t-test formula. Based on the calculation of the t-test, the researcher found out that the value of t-test was 2, 3211 and t-table was 1,697 at the degrees of freedom (19 + 18 – 2) = 35, and at the level of confidence was 0.05. Due to the fact that t-test (2, 3211) was higher than t-table (1,697), so the alternative hypothesis (H1) was accepted. There was a significant effect of whisper game technique towards students’ vocabulary mastery at eighth grade students of SMPN 3 Kota Jambi.